Risk Factors for Malnutrition in Chronic Liver Disease Patients Using RFH-NPT: A Study at Hospital Selayang, Malaysia - Abdul Hamid, Syahrul Bariah; Badrul Hisham, Nurul Syaqirah; Rajab, Norashimah (National Journal of Community Medicine, 2025)
Introduction: Malnutrition is highly prevalent among patients with chronic liver disease (CLD), affecting approximately 50-90% of cases. The Royal Free Hospital Nutritional Prioritizing Tool (RFH-NPT) is a validated screening tool for assessing malnutrition risk in CLD patients, yet its use remains limited in clinical and research settings. This study aimed to identify determinants of malnutrition risk in CLD patients at Hospital Selayang. Methods: A cross-sectional study was conducted among 85 hospitalized CLD patients from March until June 2024. Anthropometric data, including weight, height, BMI, mid-upper arm circumference, and skinfold thicknesses, were collected. Biochemical parameters were retrieved from medical records. Malnutrition risk was assessed using the validated Malay-translated RFH-NPT, while dietary intake and health-related quality of life (HRQoL) were evaluated using 24-hour recall and the SF-36 questionnaire, respectively. Data were analysed using SPSS version 29, employing descriptive statistics, Chi-square/Fisher-Exact tests, and ordinal logistic regression. Results: Significant associations were found between anthropometric data, HRQoL and malnutrition risk. Low calorie intake (OR = 25.34, p = 0.028), presence of ascites (OR = 0.076, p = 0.004), and emotional role limitation (OR = 0.114, p = 0.004) were independent predictors of malnutrition risk, all of which increased the risk. Conclusion: These findings support the clinical utility of RFH-NPT in identifying malnutrition risk among CLD patients.